Creating Identity in Women: A Psychoanalytic Reading of Namita Gokhale’s Paro: Dreams of Passions - T.G, Smitha; Dangwal, Kamlesh (Eximia, 2023)
This study is based on the theory of psychoanalytic reading, which discusses the identity of a woman in the social structure. Identity is created from the birth of a person and it continues throughout the life of that person. It is a psychological development of each person along with his/her growth. This creation of Identity starts from the relationship with the mother and later with other members of the family and society. The cultural setting also influences the person’s identity as the other members are also influenced by society. The creation of female identity is a veritable discursive concept and acquired more importance in the field of literary criticism. Searching for the identity of the female characters of Indian women authors provide an inspiration to the women of India. However, the identity of a person is always changing or adding more to his/her character along with their growth.